2022
DOI: 10.1101/2022.05.13.22275038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Green space and loneliness: a systematic review with theoretical and methodological guidance for future research

Abstract: Urban greening may help to reduce the population health impacts of loneliness and its concomitants, such as hopelessness and despair. However, the literature lacks both a critical appraisal of extant evidence and a conceptual model to explain how green space would work as a structural intervention. Both are needed to guide decision making and further research. We conducted a systematic review of quantitative studies testing associations between green space and loneliness, searching seven databases. Twenty two … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 167 publications
1
4
0
Order By: Relevance
“…These effects also reinforce pre-COVID-19 research that observed similar health outcomes in more general contexts (Lackey et al, 2021). Building on a model proposed by (Markevych et al, 2017), (Astell-Burt et al, 2022) focused on loneliness, which many people may experience in times of social distancing, to describe how experiences and opportunities in natural areas interact with individual and place-based differences to impact health and wellbeing through four broad domains: building capacities, restoring capacities, reducing harm, and causing harm. These pathways are consistent with theoretical frameworks explaining the restorative benefits of natural environments, including attention restoration (R. Kaplan & Kaplan, 1989; S. Kaplan, 1995) and stress reduction theories (Ulrich et al, 1991).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These effects also reinforce pre-COVID-19 research that observed similar health outcomes in more general contexts (Lackey et al, 2021). Building on a model proposed by (Markevych et al, 2017), (Astell-Burt et al, 2022) focused on loneliness, which many people may experience in times of social distancing, to describe how experiences and opportunities in natural areas interact with individual and place-based differences to impact health and wellbeing through four broad domains: building capacities, restoring capacities, reducing harm, and causing harm. These pathways are consistent with theoretical frameworks explaining the restorative benefits of natural environments, including attention restoration (R. Kaplan & Kaplan, 1989; S. Kaplan, 1995) and stress reduction theories (Ulrich et al, 1991).…”
Section: Discussionsupporting
confidence: 54%
“…This study joins a growing set of reviews and meta-analyses in the broader field of research examining links between nature exposure and health that are constrained from drawing concrete conclusions due to bias and quality concerns (e.g., (Astell-Burt et al, 2022;Zare Sakhvidi et al, 2022;Zhang et al, 2021). Even minor adjustments, such as improving the consistency of nature exposure's instrumentation, providing clear estimates of effects and effect sizes, and controlling for confounding could substantially reduce bias.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, recent qualitative research [32] indicates high willingness to promote nature prescriptions among mental health clinicians, but also concerns regarding multiple barriers that may challenge implementation of nature prescriptions in people living with mental illness. One such barrier might be a lack of physical access or transport to a nature space that feels safe and with qualities that attend to an individual's preferred routines [3,9,16]. A nature prescription that applies social pressure on a person to visit a space in which they feel out of place or unsafe may be a source of distress rather than restoration [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contact with nature mitigates harms (e.g. by regulating air quality [5]), restores depleted cognitive capacities [6,7], alleviates stress [8], reduces loneliness [9][10][11] and encourages regular health behaviours such as physical activity [12,13]. Meta-analyses indicate interventions that enable people to spend more time in nature increase levels of physical activity and lower risks of depression, anxiety, and high blood pressure [14], providing a compelling and urgent case to support harnessing nature in health care [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…1,10 Emerging evidence indicates that these psychological benefits may be closely entwined with restorative processes that ameliorate feelings of chronic loneliness. 13 Only one study has been conducted in general practice in Australia, in Adelaide. 14 This study involved an 8-week facilitated nature prescribing trial, first mapping green spaces locally, followed by the recruitment of 30 general practitioners (GPs) who recruited participants with chronic disease (mild-moderate diabetes or depression/anxiety).…”
Section: Evidence For Nature Prescribingmentioning
confidence: 99%